Review of the genus Oncopsis Burmeister, 1838 (Homoptera: Auchenorrhyncha: Cicadellidae: Macropsinae) of Russia and adjacent countries with description of a new species from Central Asia - Tishechkin, Dmitri Yu. (Zootaxa, 2017)
Illustrated descriptions and data on host plants and distribution for 21 species of Oncopsis of Russia and adjacent countries are given, and O. abdykulovi sp. n. from Central Asia is described. Conspecificity of O. planiscuta from East Siberia and Sakhalin,of O. tristis from Moscow Area, Alati Mts., and Sakhalin, and of O. burjatica from East Siberia and Sakhalin is corroborated by male calling signal analysis.